2019
DOI: 10.2147/dmso.s217628
|View full text |Cite
|
Sign up to set email alerts
|

<p>Usefulness Of Surrogate Markers Of Body Fat Distribution For Predicting Metabolic Syndrome In Middle-Aged And Older Korean Populations</p>

Abstract: BackgroundObesity markers, the lipid accumulation product (LAP), visceral adiposity index (VAI), triglyceride and glucose (TyG) index, and waist-to-height ratio (WHtR) are useful for assessing the risk of obesity-related cardiovascular disease. However, no previous study has assessed the usefulness of these four indices as predictors of metabolic syndrome among middle-aged and older Korean populations.PurposeTo investigate the usefulness of LAP, VAI, TyG index, and WHtR as predictors of metabolic syndrome in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 33 publications
6
33
0
1
Order By: Relevance
“…In addition, different criteria used to diagnose MetS in previous studies may also have influenced the cutoff values. The TyG index cutoff values to predict MetS in our study (8.8 in men and 8.7 in women) were very close to the findings in other studies of Asian populations [ 40 , 41 ]. The predictive value of TyG index for MetS has been reported to be inferior to VAI in previous studies, possibly because the measurement of TyG index does not include WC, a crucial marker of central obesity [ 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, different criteria used to diagnose MetS in previous studies may also have influenced the cutoff values. The TyG index cutoff values to predict MetS in our study (8.8 in men and 8.7 in women) were very close to the findings in other studies of Asian populations [ 40 , 41 ]. The predictive value of TyG index for MetS has been reported to be inferior to VAI in previous studies, possibly because the measurement of TyG index does not include WC, a crucial marker of central obesity [ 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…Notably, we found that the TyG index, a reliable surrogate marker of IR, were predictive of severe cases and mortality of COVID-19 patients. Previous studies have shown that the TyG index may predict the development of type 2 diabetes mellitus [12] and metabolic syndrome [13]. It has been reported that the TyG index is positively associated with the higher prevalence of subclinical coronary artery disease (CAD) [14], symptomatic CAD and metabolic and behavioral risk factors [15], and arterial stiffness and nephric microvascular damage [16].…”
Section: Tyg Index and The Severity And Mortality Of Covid-19mentioning
confidence: 99%
“…Previous studies have found that a high baseline TyG index was related to the development of diabetes and coronary atherosclerosis 9 11 . To our knowledge, although a cross-sectional study has recently shown that TyG index was positively correlated with MetS 12 , the relationship between TyG and MetS development has not been evaluated in the longitudinal study.…”
Section: Introductionmentioning
confidence: 96%